Cognitive bias toward the Internet: The causes of adolescents’ Internet addiction under parents’ self-affirmation consciousness - Zhou, Mindan; Zhu, Jianfei; Zhou, Zhibo; Zhou, Huiqi; Ji, Guoping (Frontiers in Psychology, 2022)
The Internet plays a crucial part in the adolescent life. However, as a product of modernization, the Internet has brought a lifestyle different from that of their parents who tend to regard excessive exposure to the Internet as a manifestation of the adolescent Internet addiction. The pride and prejudice against the Internet seem to have arisen among the parents. Under the theoretical framework of self-efficacy and empathy, this study adopts PLS-SEM to analyze the contributing factors of the adolescent Internet addiction from the perspective of self-affirmation consciousness of the parents. The results demonstrate that self-affirmation consciousness has a significant positive effect on the empathy process; the empathy process has a significant positive effect on pride and prejudice; self-affirmation has a significant positive effect on pride and prejudice; and the empathy process mediates between self-affirmation and pride and prejudice. Through the analysis on the contributing factors of the adolescent Internet addiction, this study verifies the practical effect of the empathy process in the formation of pride and prejudice with an aim to coordinate the parents with their children and make the parents have a rational understanding of both the Internet and the adolescent access to the Internet.